Nancy Fraser and the debate on socialism in the 21st century - Riela, Vanessa (Scenari, 2023)
Socialism and the 21st century are the symbolic words of the present paper: in fact, the aim of this paper is to re-signify the concept of socialism analyzing the historical rupture brought about by the great recession of 2008 through the analytical visions of Nancy Fraser, Erik Olin Wright and Gerald Allan Cohen. This dialogue provides us a multi-perspective key on socialism such as to operate a creative and critical renewal of the concept itself. In fact, the historicization of the mentioned notion turns out to be a necessary requirement without which any attempt to rethink socialism would be in vain and unsuccessful.